Assessing the Impact of Electoral and Administrative Reforms on Indian Democracy - A Review (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This review article provides an analysis and evaluation of the effects that electoral and administrative changes have had on the democratic system in India. Electronic Voting Machines (EVMs), voter identity cards, decentralization via Panchayati Raj institutions, digitization of government services, and anti-corruption initiatives like as the Right to Information (RTI) Act, Lokpal, and Lokayuktas Act are some of the important changes that are discussed in this report. Elections are a crucial aspect of a democratic polity, reflecting the attitudes, values, and beliefs of the people towards their political environment. They grant the people the right to govern and are the central democratic procedure for selecting and controlling leaders. Elections allow the people to express their faith in the government and change it as needed. They symbolize the sovereignty of the people and provide legitimacy to the government's authority. Free and fair elections are indispensable for the success of democracy, as mandated by the Constitution for parliamentary democracy. The growth of a democratic polity can only be achieved through a content of free, fair, and effective election processes in the legislative bodies. This article examines the success of these changes in promoting transparency, accountability, public involvement, and governance efficiency within India's democratic framework. It delves into the obstacles that these reforms face as well as the implications that they have. In addition to this, it addresses possible areas for additional reform efforts and changes to be made in order to boost elections in India.